Neuroscience and reductionism: Some realist reflections - Paul K. Edwards (University of Birmingham, Birmingham Business School, 2013)
Organizational neuroscience (ON) is a rapidly emerging sub-field. Criticisms of its reductionism are common. Yet it is possible for practitioners and critics to engage. Such engagement is facilitated by realism. It agrees with the practitioners of ON that brain functions can in principle be measured and that causal influences can be identified. It agrees with the critics in stressing the centrality of context and the emergent nature of social processes. The claims and potentials of ON can best be grasped through realist principles.
Keywords: 330; Emergence; Neuroscience; Organizational neuroscience; Realism